ارتباط التكيف الاجتماعى لدى اهالى الفاقدين لأبنائهم من الضفة الغربية والقدس فى فلسطين جراء الموت المفاجئ بعدد أفراد الأسرة ونوع الولد المتوفى - وتد، صلاح الدين علي; مصطفى، روان (جامعة قاصدي مرباح - ورقلة, 2015)
This study aims to understand as well as acknowledge the differences of social cooping among the parents who lost their offspring to sudden death from the West bank and Jerusalem and the number of the family’s members as well as the gender of the deceased individual. The method of social scanning was used and a sample of 298 fathers and mothers who lost their offspring due to sudden death. And agreed to participate in this research which is divided according to the following regions: Jerusalem; Bethlehem, Hebron; Ramallah; Nablus and Jericho. As well as, the villages, camps and towns from the West Bank. The results showed that there is a significant difference that can be measured to the extent of social cooping of among the parents and the number of the family members whereas, the cooping is faster among the families that has large members. On the other hand, the results indicate that there are no significant differences in the social cooping which allocated to the gender of the deceased individual. Therefore, the children are all equal if deceased to their parent’s cooping.
تهدف هذه الدراسة إلى محاولة التعرف على وجود فروق في التكيُّف الاجتماعيّ لدى الوالدين الفاقدين لأبنائهم جرّاء الموت المفاجئ من الضفة الغربيّة والقدس بعدد أفراد الأُسرة، وجنس الولد المُتوفي. وتمّ استخدام منهج المسح الاجتماعيّ، وتكوّنت العينة من (298) من الآباء والأمهات الذين فقدوا أبناءهم جرّاء الموت المفاجئ، ووافقوا على المشاركة في البحث موزعة على مناطق: القدس، وبيت لحم، والخليل، ورام الله، ونابلس، وأريحا. ما بين مدن وقرى ومخيمات. وأشارت النتائج إلى وجود فروق ذات دلالة إحصائيّة في مدى التكيُّف الاجتماعيّ للوالدين تُعزى إلى عدد أفراد الأُسرة حيث يكون التكيُّف أسرع في الأُسر الأكبر حجما. بينما تبيّن عدم وجود فروق في التكيُّف الاجتماعيّ تُعزى إلى جنس الولد المتوفي، فالأبناء أسوياء في فقدانهم على تكيف والديهما.
Keywords: التكيف الإجتماعى -- الموت المفاجئ -- الضقة الغربية -- القدس